On the cliffs of Foxglove Manor - Wright, Jaime Jo (Bethany House, a division of Baker Publishing Group, 2021)
"In search of her father's lost goods, Adria encounters an eccentric old woman who has filled Foxglove Manor with dangerous secrets that may cost Adria her life. Centuries later, when the senior residents of Foxglove under her care start sharing chilling stories of the past, Kailey will have to risk it all to banish the past's demons, including her own"--